DOES WOMEN PARTICIPATION ON BOARDS IS ENOUGH TO IMPROVE THE FIRM PERFORMANCE? - Muhammad Harddisk Bintang Zulfikar; Vita Elisa Fitriana (Universitas Muhammadiyah Jember, 2020)
This research aims to examine the impact of women participation in theboards of director (BOD) on the performance of the firms. Whether the presence ofwomen in BOD could make the performance of the firms become better or worse.Furthermore, the present study also wants to fills the gaps in the extant literature byexamining the moderating effect of working experience in the relationship betweenwomen participation in BOD and firm performance. This research is a secondary dataanalysis which is using 280 service companies listed on Indonesia Stock Exchange(IDX) for the year 2014-2017 as its sample. This research use multiple linearregression. The result shows that working experience of the women boards is positivelyinfluence the relationship of women participation on boards with the firm performance.This result is expected can make the stakeholder of organization aware of the benefithaving more gender diverse boards.